Ions substitution effect on the magnetic phase transition temperature of 0.5BiFeO3-0.5Pb1-xSrxTiO3 multiferroic solid solutions. Issue 1 (19th May 2021) - Raevskaya, S. I.; Kubrin, S. P.; Zhuang, J.; Raevski, I. P.; Bikyashev, E. A.; Malitskaya, M. A.; Zakharchenko, I. N.; Titov, V. V.
Abstract: 0.5BiFeO3 -0.5Pb1-x Srx TiO3 (0 ≤ x ≤ 1) solid solution compositions were synthesized using solid phase reactions route from high-purity oxides. Mössbauer studies showed that for 0.5BiFeO3 -0.5PbTiO3 ( x = 0) the magnetic phase transition temperature T M value was about 130 K. Substitution of Sr for Pb led to a dramatic decrease in T M, though the Fe content did not change with x and for 0.5BiFeO3 -0.5SrTiO3 ( x = 1) T M was only ≈20 K. This dramatic difference in T M values seems to be due to additional contribution of the magnetic superexchange between Fe 3+ ions via the empty 6p states of Bi 3+ and Pb 2+ ions to the overall superexchange.